2007
DOI: 10.1097/01.aog.0000249607.82768.a1
|View full text |Cite
|
Sign up to set email alerts
|

Retropubic Compared With Transobturator Tape Placement in Treatment of Urinary Incontinence

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 31 publications
1
74
1
6
Order By: Relevance
“…The complication rates are higher with retropubic routes than with transobturator tapes (26), although there are some studies against this conclusion (27,28,29). For instance, a randomized comparative trial suggested that patients in transobturator group had more complications than the retropubic group (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complication rates are higher with retropubic routes than with transobturator tapes (26), although there are some studies against this conclusion (27,28,29). For instance, a randomized comparative trial suggested that patients in transobturator group had more complications than the retropubic group (27).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a randomized comparative trial suggested that patients in transobturator group had more complications than the retropubic group (27). However, in another study, it was demonstrated that TOT was equally effective as TVT with fewer complication, and the authors suggested that TOT would be the procedure of choice (30).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the definition used to define cure, the objective and subjective cure rates appear to be statistically similar with all sling modalities for the uncomplicated patient with stress incontinence. [5][6][7][8][9][10] There does, however, appear to be a significant difference in complications between the approaches. The retropubic approach demonstrates an increased risk of intraoperative bladder perforations, de novo urgency and storage lower urinary tract symptoms (LUTS), while transobturator routes show an increased risk of vaginal erosion and groin pain.…”
Section: Short-and Long-term Outcomesmentioning
confidence: 99%
“…Bu nedenle ,literatüre katkı sağlaması amacıyla, kendi kliniğimizde asistanların uzman eşliğinde yaptığı midüret-ral slingleri komplikasyon ve tedavi oranları açısından inceledik. Midüretral sling operasyonlarında kanama insidansı tanıma bağlı değişmekle birlikte, TVT sonrası %0.7-8 arasında [14,15], TOT sonrası ise %0-2 arasında bildirilmiştir [16,17].Bizim çalış-mamızda, 91 TVT yapılan hastanın 3(%3.3) ünde transfüzyon gerektiren kanama izlenirken, 50 TOT yapılan hiçbir hastada transfüzyon gerektiren kanama izlenmedi. TVT yapılan ve transfüzyon gerektiren 3 hastadan birinde, postoperatif 4.saatte kanama nedeniyle laparotomi yapıldı.…”
unclassified
“…Bu nedenle, TVT yapılan hastalar postoperatif erken dönemde korona mortis ve majör damar yaralanmaları açısından yakından izlenmelidir. Literatürde, mesane perforasyonu insidansı TVT için %0.7-34.2 arasında [14,21], TOT için %0-3.1 [22,23] olarak bildirilmiştir. Bizim çalışmamızda, mesane perforasyonu insidansı TVT için %5.5(5/91) iken, TOT yapılan 50 hastada hiç mesane perforasyonu izlenmemiştir.…”
unclassified